2007
DOI: 10.1021/jp0717701
|View full text |Cite
|
Sign up to set email alerts
|

Methanol Adsorption and Dissociation on TiO2(110) from First Principles Calculations

Abstract: In this work we report on theoretical calculations of methanol adsorption and dissociation on the stoichiometric and defective TiO2(110) surface. The periodic implementation of density functional theory (DFT) with plane waves and pseudopotentials was employed. A supercell made of 4 × 1 unit cells was used to represent the surface, which corresponds to methanol coverage of 0.25 ML. The defective surface was modeled by removing one bridging oxygen from the outermost layer. Several adsorption sites were explored … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
63
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(72 citation statements)
references
References 31 publications
8
63
0
Order By: Relevance
“…80,81,83 Most DFT calculations show that the transfer of the hydroxyl protons from methanol to the neighboring bridge oxygen sites has a small barrier and the dissociated state of methanol is nearly iso-energetic to the molecular adsorbed state, with the dissociated state being at a slightly higher energy. This suggests that the methanol molecules should be adsorbed on the TiO 2 (110) surface in a molecular form at low temperatures, which is consistent with STM experiments at both room temperature and liquid nitrogen temperature.…”
Section: Adsorption Of Methanol On Tio 2 (110)mentioning
confidence: 99%
See 2 more Smart Citations
“…80,81,83 Most DFT calculations show that the transfer of the hydroxyl protons from methanol to the neighboring bridge oxygen sites has a small barrier and the dissociated state of methanol is nearly iso-energetic to the molecular adsorbed state, with the dissociated state being at a slightly higher energy. This suggests that the methanol molecules should be adsorbed on the TiO 2 (110) surface in a molecular form at low temperatures, which is consistent with STM experiments at both room temperature and liquid nitrogen temperature.…”
Section: Adsorption Of Methanol On Tio 2 (110)mentioning
confidence: 99%
“…Therefore, the physical and chemical properties of methanol on TiO 2 (110) have been examined in detail both experimentally 29,53,62,[73][74][75][76][77][78][79] and theoretically [80][81][82][83][84] to probe the active sites and relevant reactive structures. Despite this extraordinary effort, central questions remain unresolved, for example, how methanol enhances the photocatalysis of water or how it is eventually photodegraded on TiO 2 .…”
Section: Photocatalysis Of Methanol On Tio 2 (110)mentioning
confidence: 99%
See 1 more Smart Citation
“…[4][5][6][7][8] Among them, methanol on TiO 2 has attracted much attention in both experimental [9][10][11][12] and theoretical [13][14][15][16][17] investigations because of the remarkable enhancement effect in photocatalyzed hydrogen production in the mixture of methanol with water. 18 Dissociation of methanol on bridge-bonded oxygen vacancy sites (BBOv's) 19 of TiO 2 (110) surfaces has been observed by scanning tunneling microscopy (STM), and this suggests that spontaneous dissociation at these oxygen vacancy sites is possible, in accordance with the recent results of theoretical calculations.…”
Section: ) Introductionmentioning
confidence: 99%
“…Many previous experiment and calculation investigations of CH 3 OH dissociation on the surfaces suggested that the O-H scission was proposed as the initial dissociation step [4,10], C-H scission was more favorable than O-H scission [11,12], and the C-O scission suggested to be impossible one for both experimental and theoretical studies [9,11,[13][14][15]. However, CH 3 OH dissociation through three routes of bond scission on 2Cu/ZnO   0 1 10 surface in this present works is not still found.…”
mentioning
confidence: 99%